Economic Analysis and Livelihood Improvement Strategies for Vegetable Cultivators in Svay Rieng and Svay Chrum Districts, Cambodia - Chanthan Or; Putheasath Sin; Chhun Hong; Vanchey Ros; Tithya Kang; Dina Pen; Mardy Serey; Hendra Prasetyo; Sri Maryati (PT. Altaf Publishing Corp, 2025)
Smallholder farmers in Svay Rieng Province, Cambodia, play a crucial role in the country's agricultural sector, particularly in vegetable production. Despite facing numerous challenges such as limited access to resources, climate change, and market uncertainties, these farmers contribute significantly to the national food security. This study aims to explore the technical knowledge, technical adaptation and practices of vegetable cultivation, and to analyze the economic efficiency of vegetable cultivation of farmers in Svay Rieng and Svay Chrum districts, Svay Rieng province, Cambodia. The household survey was conducted on 92 farmers in ten target communities, with at least three types of vegetables planted by each household. The result revealed that nearly two-thirds of farmers have over nine years of experience in vegetable cultivation, with most receiving technical training from the HEQCIP Project team. Nearly 70% of non-target farmers received training from government agencies and NGOs. A high percentage of survey farmers (90% target farmers and 75% non-target farmers) share their technical knowledge and experiences on vegetable cultivation with their relatives, neighbors, and other farmers in their communities. At least three different types of vegetables were planted by each household in target communities, including onion leaf, cucumber, wax gourd, gourd, cabbage, luffa gourd, herbs, morning glory, eggplant, pumpkin, spiny, and long-bean. The percentage of farmers who applied techniques provided by the project to integrate with their experiences was high (76% target farmers and 52% non-target farmers). However, only 17% target and 11% non-target farmers adapted the full technical packages provided by the project. The survey found that 75% of target and 50% non-target farmers improved their livelihood status, with 50% using their incomes from vegetable selling for income generation activities, 80% for purchasing household materials and equipment, and 10% for repaying in-debts.